Seksualitas dan Negara: Permasalahan Dispensasi Perkawinan Anak di Indonesia - Wahyudi, Tri Hendra; Prastiwi, Juwita Hayyuning (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2022)
The Revision of the Marriage Law has improved the marriage age limit for women from initially 16 years old became 19 years old. But in fact, the limit change has not been able to reduce the number of child marriages in Indonesia. Since the Law number 16 of 2019 has been ratified for two years, child marriage has actually increased. Various conflicting factors have become the roots of child marriage, one of which is regulatory loopholes through the article of marriage dispensation. This study reviews the phenomenon of child marriage, focused primarily on how the marriage dispensation policy works. This problem is analyzed using the theory of power and sexuality from Michel Foucault and a feminist perspective. Under the feminist research methodology paradigm, the study was conducted qualitatively through the literature review method. As a result, the practice of state power over sexuality (the episteme of political power) appears to be strongly influenced by the first-tier episteme (religion). At the community level, various reasons for proposing a marriage dispensation, such as poverty, low education, and traditions are legitimized by the influence of religious interpretations which allow child marriage. Distracted by the condition of the community, the government, which should ideally be a barrier to child marriage, actually granted the majority of marriage dispensation applications. The strong first-tier episteme is also reflected by the consideration of judges who grant marriage dispensation. Therefore, the government has contributed to increasing the number of child marriages. As a solution, the House of Representatives through its oversight function can encourage the government to implement a gender perspective through a national strategy that has been proclaimed, as well as encourage the government to increase the number of female judges in the Religipus Courts.AbstrakRevisi UU Perkawinan telah menghasilkan kemajuan pada batas usia perkawinan bagi perempuan, dari awalnya 16 tahun menjadi 19 tahun. Namun faktanya, perubahan batas usia perkawinan belum mampu menekan angka perkawinan anak di Indonesia. Dalam kurun dua tahun sejak UU Nomor 16 Tahun 2019 disahkan, perkawinan anak justru mengalami peningkatan. Berbagai faktor saling sengkarut menjadi akar perkawinan anak, salah satunya adalah celah regulasi melalui pasal dispensasi kawin. Kajian ini mengulas fenomena perkawinan anak, berfokus terutama pada bagaimana kebijakan dispensasi perkawinan bekerja. Persoalan tersebut dianalisis menggunakan teori kekuasaan dan seksualitas dari Michel Foucault dan perspektif feminis. Di bawah paradigma metodologi penelitian feminis, kajian dilakukan secara kualitatif melalui metode literature review. Sebagai hasilnya, praktik kuasa negara terhadap seksualitas (episteme kekuasaan politik), tampak kuat dipengaruhi episteme lapis pertama (agama). Pada level masyarakat, berbagai sebab pengajuan dispensasi kawin seperti kemiskinan, rendahnya pendidikan, serta tradisi, dilegitimasi pengaruh tafsir agama yang membolehkan perkawinan anak. Gayut dengan kondisi masyarakat, pemerintah yang idealnya menjadi perintang perkawinan anak justru mengabulkan mayoritas pengajuan dispensasi kawin. Kuatnya episteme lapis pertama, juga tergambar pada pertimbangan hakim yang mengabulkan dispensasi kawin. Harus diakui bahwa pemerintah telah turut berkontribusi dalam peningkatan jumlah perkawinan anak. Sebagai solusi, DPR RI melalui fungsi pengawasan dapat mendorong pemerintah mengimplementasikan perspektif gender dalam strategi nasional yang telah dicanangkan, serta mendorong pemerintah memperbanyak jumlah hakim perempuan di Pengadilan Agama.